Poly(ADP-ribose) polymerase inhibitor induces accelerated senescence in irradiated breast cancer cells and tumors - Efimova, Elena V. (2010)
Persistent DNA double strand breaks (DSBs) may determine the anti-tumor effects of ionizing radiation (IR) by inducing apoptosis, necrosis, mitotic catastrophe or permanent growth arrest. Ionizing radiation (IR) induces rapid modification of megabase chromatin domains surrounding double strand breaks (DSBs) via poly-ADP-ribosylation, phosphorylation, acetylation, and protein assembly. The dynamics of these ionizing radiation-induced foci (IRIF) have been implicated in DNA damage signaling and DNA repair. As an IRIF reporter, we tracked relocalization of GFP fused to a chromatin binding domain of the checkpoint adapter protein 53BP1 after IR of breast cancer cells and tumors. To block DSB repair in breast cancer cells and tumors, we targeted poly(ADP-ribose) polymerase with ABT-888 (veliparib), one of several PARP inhibitors currently in clinical trials. PARP inhibition markedly enhanced IRIF persistence and increased breast cancer cell senescence both in vitro and in vivo, arguing for targeting IRIF resolution as a novel therapeutic strategy.